Enhancement of Heat Transfer Performance For Parabolic Trough Solar Collector with Pin Fin Arrays Inserting - Dubey, Mukesh Dhar; Kumar, Amit (Innovative Research Thoughts, 2018)
Heat dissipation is one of the main problems which we come across while dealing with high load and high speed machines. Because of the work they perform, some amount of heat is generated inside the machine. This heat has to be transferred outside the system to obtained efficient output. If it is not done, then this heat may cause damage to machine parts. To do this, fins are used. Main purpose of fins is to increase surface area of machine so that heat can be transmitted in atmosphere. Tube receiver with pin fin arrays inserting was introduced as the absorber tube of parabolic trough receiver to increase the overall heat transfer performance of tube receiver for parabolic trough solar collector system. The Monte Carlo ray tracing method (MCRT) coupled with Finite Volume Method (FVM) was adopted to investigate the heat transfer performance and flow characteristics of tube receiver for parabolic trough solar collector system.